Status of Health Discipline Students to Receive Training on Occupational Health and Safety and Exposure to Occupational Accident - Cemile Savcı; Gülser Şerbetçi; Ümmühan Kılıç (Association of Nurse Managers, 2018)
INTRODUCTION: The study was conducted to determine the level of awareness and knowledge of occupational health and safety for health discipline students who were admitted to practice at health facilities and to plan and direct training activities to prevent occupational accidents at health facilities. METHODS: The study was descriptive and included 452 health discipline students, aged 18 years and over, who were continuing clinical practice training at 12 health facilities affiliated to the General Secretariat of Istanbul Beyoğlu Region Public Hospitals Association between 23.11.2016 / 23.02.2017. he data were collected using the "Structured Information Form" which was developed under the guidance of literature and composed of 23 questions. RESULTS: It was found that 90.5% of the students (n = 409) were educated about "Occupational Health and Safety" before the clinical practice in the school or the institution they were going to practice, and who were exposed to work accidents at the rate of 80.9% (n = 51) 76,1% (n = 48) of them were students in Nursing department. Of the trainees (n= 409) 12.46% (n = 51) were exposed to work accidents while 27.90% (n = 12) were injured among untrained students (n = 43). DISCUSSION AND CONCLUSION: As a result, it was found that the occupational accident exposure of the students who received Occupational Health and Safety education was less.